Controllability and second-order necessary conditions for optimality. (January 2019) - Avakov, E. R.; Magaril-Il'yaev, G. G.
Abstract: Sufficient conditions for the local controllability of a control system of ordinary differential equations are presented. These conditions are meaningful in the case where the linear approximation of the system is not completely controllable. Second-order necessary conditions for optimality for the problem of optimal control are obtained as a corollary. Bibliography: 13 titles.